Optimización de las líneas de producción quesera de las microempresas ubicadas en la parroquia Pucayacu del cantón la Maná - Cuesta Masapanta, Cristhina Geovanny (2020)
In this present research he discloses the "OPTIMIZATION OF THE PRODUCTION LINES THAT ARE THE MICROCOMPANIES LOCATED IN THE PUCAYACU PARISH OF THE CANTON LA MANA" in the Province of Cotopaxi. For this research it is proposed objectives to help analyze each of them, in order to take advantage of the resources and innovate this livestock sector, the interview that was conducted with the managers or owners of the 3 micro-enterprises of dairy products, t was determined that the processing of milk products favors different social groups being a form of economic income for most of that locality, the factors that affect is technological innovation in the different areas of cheese production and others, the sites to be offered will be in entrepreneurs to micro-enterprises dedicated to the manufacture of dairy products. The sites where the renewal or automation of technology will be promoted are in three of the most recognized micro-enterprises of the place (Productos lácteos 3k, Quesos Marielita y Asociación de productos Lácteos la Josefina) is where you will propose the innovation of the production areas and the correct relocation of the processing lines, carrying out the following activities involved in the research that are the following : milk reception, milk transfer, milk measurement, add curd, coagulation, curd cut, desuerated, add salt, kneading, backaging, storage in the cold room. Once the production line was identified by careful information (process diagrams and plans) from each of them, the different areas could be proposed to the innovation of equipment and machinery in the activities studied and the relocation of them taking into account existing standards in order to provide safety to workers and the optimization of processes to obtain a quality product. By performing a financial statement, the feasibility and profitability of the project is demonstrated.